Health and well-being issues of Nepalese migrant workers in the Gulf Cooperation Council countries and Malaysia: a systematic review. Issue 10 (26th October 2020) - Paudyal, Priyamvada; Kulasabanathan, Kavian; Cassell, Jackie A; Memon, Anjum; Simkhada, Padam; Wasti, Sharada Prasad
Abstract : Objective: To summarise the evidence on health and well-being of Nepalese migrant workers in the Gulf Cooperation Council (GCC) countries and Malaysia. Design: Systematic review. Data sources: EMBASE, MEDLINE, Scopus and Global Health databases. Eligibility criteria: Studies were eligible if they: (1) included Nepalese migrant workers aged 18 or older working in the GCC countries or Malaysia or returnee migrant workers from these countries; (2) were primary studies that investigated health and well-being status/issues; and (3) were published in English language before 8 May 2020. Study appraisal: All included studies were critically appraised using Joanna Briggs Institute study specific tools. Results: A total of 33 studies were eligible for inclusion; 12 studies were conducted in Qatar, 8 in Malaysia, 9 in Nepal, 2 in Saudi Arabia and 1 each in UAE and Kuwait. In majority of the studies, there was a lack of disaggregated data on demographic characteristics of Nepalese migrant workers. Nearly half of the studies (n=16) scored as 'high' quality and the rest (n=17) as 'moderate' quality. Five key health and well-being related issues were identified in this population: (1) occupational hazards; (2) sexual health; (3) mental health; (4) healthcare access and (5) infectious diseases. Conclusion: To our knowledge, this is the most comprehensive review of the health and well-being of Nepalese migrant workers in the GCC countries and Malaysia. This review highlights an urgent need to identify and implement policies and practices across Nepal and destination countries to protect the health and well-being of migrant workers.